The Concept of Human Equality and Gender an Islamic Perspektive in a Multicultural Society - Arif Luthfi, Muhammad; Rohimin, Rohimin; Suradi, A.; Khoiri, Qolbi; Destriani, Destriani (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
This study aims to describe how Muslims in a multicultural society interpret and experience human and gender equality within the framework of Islamic values. Employing a qualitative conceptual-phenomenological approach, the research draws on in-depth interviews, participant observation, and documentation to examine how principles of justice and human dignity are translated into social practice. The findings reveal that human equality in Islam is normatively understood as equality of worth, yet its application remains influenced by patriarchal cultural norms, particularly in role distribution and access to public spheres. The study also finds that gender equality is perceived as “role balance” rather than absolute sameness, while Islamic educational institutions and women’s organizations serve as key arenas for the contextual reinterpretation of gender equality. The interaction between Islamic teachings and local cultural values produces a gradual shift toward more egalitarian gender relations. The study concludes that Islamic gender equality is inclusive and dynamic, with strong potential to enhance social justice when supported by progressive educational and religious practices. These findings indicate the need for strengthened multicultural-based policies and educational strategies to promote more gender-just communities.